BUILDING A MEGACITY: JAKARTA IN THE 21ST CENTURY A CASE STUDY OF THE URBAN TRANSPORT SYSTEM IN JAKARTA - Negara, Siwage Dharma (P2E-LIPI, 2015)
Jakarta is rapidly becoming as one of the worldâs megacities and this has been boosted by its impressive economic growth over past decades. The city has transformed over the past thirty years into one of the modern financial and services hubs in Southeast Asia. With a population of more than ten million, it is now a thriving centre of entrepreneurship. However, the city is striving to find a balance between growth and sustainable development. Like all other megacities, Jakarta faces serious development challenges, such as a population explosion, traffic congestion, environmental pollution, resource shortages, urban poverty and cultural conflicts. This study focuses on the complex challenge of alleviating worsening traffic congestion in Jakarta. It looks at how various fragmented policies and strategies have failed to solve this problem because of poor planning, lack of community participation, poor urban transport management and unbalanced regional development. In particular, it addresses the key failure to develop a sustainable urban transport system that considers the social, economic, environmental and cultural elements of the city. The essential message of the study is that to control traffic congestion successfully, reforms in the urban transport system should be complemented with more community engagement in planning, governance and monitoring. Social sciences can contribute to the understanding of the problems and reinforce the necessity for wide-ranging social and behavioural reforms in urban society